3-(2,4-Dichlorophenyl)-1-(4-methoxyphenyl)prop-2-en-1-one - Rosli, Mohd Mustaqim; Patil, P. S.; Fun, Hoong-Kun; Razak, Ibrahim Abdul; Puranik, Vedavati G.; Dharmaprakash, S. M. (Acta Crystallographica Section E-Structure Reports Online, 2006)
In the title compound, C16H12Cl2O2, the dihedral angle between the benzene rings is 28.63 (6)degrees. The crystal structure is stabilized by intermolecular C-H center dot center dot center dot O hydrogen bonds and by short Cl center dot center dot center dot Cl interactions.